Value-Based Leadership Redefined: Driving Engagement and Teacher Performance Through Ethical Climate in Private Islamic Senior High School - Nurdelima Waruwu (Journal of Education and Teaching (JET), 2025)
Authentic leadership (AL) plays a crucial role in enhancing teacher engagement and performance by fostering a conducive ethical climate (EC). However, further examination is needed in the context of Madrasah Aliyah.  This study aims to explain the mediating role of EC in the relationship between AL, teacher engagement, and performance. An explanatory survey was conducted online (39%) and offline (61%) with 282 randomly selected, permanently employed private Madrasah Aliyah teachers in West Java. Data were collected via Google Forms and printed questionnaires during teacher meetings and analyzed using covariance-based Structural Equation Modeling (SEM). Findings indicate that EC mediates the relationship between AL, teacher engagement, and performance. Additionally, work engagement (WE) mediates the influence of AL on performance and partially mediates the effect of EC on performance. By integrating the Job Demands-Resources (JD-R) Model with Value-Based Leadership, this study clarifies the link between AL, EC, and teacher engagement. AL serves as an organizational resource strengthened by EC. To sustain teacher engagement and performance, multi-level training programs should expand AL practices among principals and senior teachers. MAS fosters EC through transparency, fairness, and value-based leadership.